Social welfare institutions strategy in shaping social behavior of children with legal problems in Bima - Irawan, Bambang; Martitah, Martitah; Arsal, Thriwaty (Universitas Negeri Semarang, 2024)
The social welfare institution known as LPKS plays a crucial role in providing protection and guidance to children, though its implementation remains suboptimal. This discussion focuses on the LPKS strategy in shaping the social behavior of children with legal issues and the factors hindering its effectiveness. This research employs a qualitative descriptive method with a phenomenological approach, involving direct field observations, interviews, and documentation. The findings regarding the LPKS strategy in shaping the social behavior of children with legal problems include several aspects. Firstly, there is a normative role. Secondly, LPKS performs a practical role by addressing various needs such as mentoring, psychological therapy, spiritual or religious therapy, arts training activities, and legal protection throughout the legal process. Additionally, it provides educational guidance focusing on the developmental and mental aspects of children. Finally, the ideal role is to enhance LPKS performance. The primary inhibiting factor affecting the LPKS strategy in shaping the social behavior of children with legal problems is budget limitations. These limitations arise due to the substantial budget required to cover a large area, while existing resources remain insufficient.